2007
DOI: 10.1038/sj.ijo.0803689
|View full text |Cite
|
Sign up to set email alerts
|

Clock genes are implicated in the human metabolic syndrome

Abstract: Background: Clock genes play a role in adipose tissue (AT) in animal experimental models. However, it remains to be elucidated whether these genes are expressed in human AT. Objective: We investigated the expression of several clock genes, Bmal1, Per2 and Cry1, in human AT from visceral and subcutaneous abdominal depots. A second objective was to elucidate whether these clock genes expressions were related to the metabolic syndrome features. Methods: Visceral and subcutaneous AT samples were obtained from morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 35 publications
8
91
0
2
Order By: Relevance
“…[40][41][42][43][44][45] It has also recently been reported that the expression of several components of the molecular clock (Per2,Cry1, Bmal1) in adipose tissue are associated with features of the metabolic syndrome in man. 46 …”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43][44][45] It has also recently been reported that the expression of several components of the molecular clock (Per2,Cry1, Bmal1) in adipose tissue are associated with features of the metabolic syndrome in man. 46 …”
Section: Discussionmentioning
confidence: 99%
“…20,21,26,[31][32][33] Circadian-clock genes are associated with the pathophysiology Diet-induced obesity on circadian-clock systems M-C Hsieh et al of metabolic syndrome due to impairment of adipogenesis by a deficiency in Bmal1. 34 Deletion of Bmal1 also induces arrhythmicity, early onset of age-related pathologies, including myopathy and arthropathy, and altered hepatic carbohydrate metabolism; 20,35,36 Clock-mutant mice are hyperphagic and obese, and similarly develop metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be the fact that components such as the wake-sleep cycle, thermogenesis, food intake, and lipid and glucose metabolism are under circadian regulation. This regulation synchronises available and expenditure energy to external changes in the environment, such as the light -dark phase (15) . Such rhythms are coordinated by circadian clocks which are intrinsically maintained by molecular mechanisms whose objective is to condition humans to adapt to environmental changes.…”
Section: The Impact Of Shift Work On Anthropometric Parametersmentioning
confidence: 99%